2023
DOI: 10.1371/journal.pone.0284182
|View full text |Cite
|
Sign up to set email alerts
|

Comparative assessment of regional tau distribution by Tau-PET and Post-mortem neuropathology in a representative set of Alzheimer’s & frontotemporal lobar degeneration patients

Abstract: Flortaucipir (FTP) PET is a key imaging technique to evaluate tau burden indirectly. However, it appears to have greater utility for 3R+4R tau found in Alzheimer’s disease (AD), compared to other non-AD tauopathies. The purpose of this study is to determine how flortaucipir uptake links to neuropathologically determined tau burden in AD and non-AD tauopathies. We identified nine individuals who had undergone antemortem tau-PET and postmortem neuropathological analyses. The cohort included three patients with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…However, as mentioned above, it is still unknown whether flortaucipir binds to 4RT in tauopathies such as PAOS. Previous studies have also shown that flortaucipir has limitations in the representation of neuropathological assessment of tau burden in brain regions with low tau, like atypical AD cases (Gatto, Carlos, et al, 2023 ; Gatto, Martin, et al, 2023 ). On a technical note, the coregistration of different imaging modalities imposes limitations and technical challenges, particularly considering a spatio‐temporal approximation of two different physical events; one determined by the velocity of water diffusion and a second based on the radioactive decay signal from a molecular ligand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as mentioned above, it is still unknown whether flortaucipir binds to 4RT in tauopathies such as PAOS. Previous studies have also shown that flortaucipir has limitations in the representation of neuropathological assessment of tau burden in brain regions with low tau, like atypical AD cases (Gatto, Carlos, et al, 2023 ; Gatto, Martin, et al, 2023 ). On a technical note, the coregistration of different imaging modalities imposes limitations and technical challenges, particularly considering a spatio‐temporal approximation of two different physical events; one determined by the velocity of water diffusion and a second based on the radioactive decay signal from a molecular ligand.…”
Section: Discussionmentioning
confidence: 99%
“…Previously described criteria were applied for selecting the number of optimal seed points (Cheng et al, 2012 ; Zajac et al, 2017 ). An average of 500,000 seeds were placed with a distance voxel tolerance of 16 mm as performed before (Gatto, Carlos, et al, 2023 ; Gatto, Martin, et al, 2023 ; Gatto et al, 2024 ). Whole‐brain deterministic fiber tracking algorithms with augmented tracking strategies to improve reproducibility were calculated (Yeh et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…Promising clinical trials targeting tau and TDP-43 in FTD are a unique opportunity to find therapeutics in neurodegeneration.105 Tau-antibodies, tau phosphorylation and acetylation inhibitors, tau vaccines, and microtubule-stabilizing agents are currently underway in various phases of 8 Younes & Miller development. 7,28,29 Moreover, innovative gene-editing therapies using antisense oligonucleotides (synthetic nucleic acids that can inactive the mRNA of a target gene) to reduce C9orf72 expansion or increase PRGN expression in patients with genetic FTD are in active investigation and development. 27 Molecule-based therapies are under consideration for the genetic forms of Frontotemporal Dementia (FTD) and for addressing the symptoms of the disease (refer to Table 2).…”
Section: Current Clinical Trials and Biomarkersmentioning
confidence: 99%